Improvement of human platelet aggregation post-splenectomy with paraesophagogastric devascularization in chronic hepatitis B patients with cirrhotic hypersplenism - Hui Zhang; Shaoying Zhang; Jian Zhang; Rui Zhou; Yongzhan Nie; Song Ren; Jun Li; Keping Feng; Fanpu Ji; Guangyao Kong; Zongfang Li (Platelets, 2020)
Thrombocytopenia is a common hematological abnormality in patients with cirrhotic hypersplenism. Splenectomy with paraesophagogastric devascularization (SPD) is a conventional surgical therapy which can reverse pancytopenia in these patients. Platelets are traditionally recognized for their central role in hemostasis. However, the status of platelet aggregation in chronic hepatitis B patients with cirrhotic hypersplenism before and after SPD has not been reported yet. A total of 41 cirrhotic patients and 31 healthy controls were included in this study. Platelet aggregation was detected by AggRAM® Advanced Modular System (Helena Laboratories, USA). ELISA was used to detect the cytokines closely related to platelet aggregation. Expressions of platelet membrane glycoproteins (GPs) were evaluated by flow cytometric analysis. Platelet aggregation was found to be decreased distinctly in the cirrhotic patients, and to be restored to normal level after SPD. The cirrhotic patients showed higher plasma levels of the cytokines HMGB1, PEDF, vWF, cAMP and cGMP, which also improved partially after SPD. Moreover, the cirrhotic patients had much lower expression of GPIIb/IIIa, GPIbα and P-selectin than either the healthy controls or SPD patients at basal or activated level. Generally, SPD benefits cirrhotic patients with bleeding tendencies by improving platelet counts and aggregation. GPIIb/IIIa may be the key membrane protein responsible for the change in platelet aggregation before and after SPD.